The temporal association between suicide and comorbid mental disorders in people treated for substance use disorders: a National registry study - Martin Ø. Myhre; Fredrik A. Walby; Jørgen G. Bramness; Lars Mehlum (Addiction Science & Clinical Practice, 2023)
Abstract Background The time after contact with specialized health services for mental health and substance use is associated with an increased risk of suicide, where temporal aspects of suicide and comorbid mental disorders in patients with substance use disorders could be associated. This study aimed to examine the temporal association between time from last treatment contact to suicide and comorbid mental disorders in patients with substance use disorders. Methods This study is a historical prospective case series using nationwide registry data. It included 946 individuals registered the year before suicide with a substance use disorder (F10-F19) in Norway's specialized health services for treating substance use and mental health disorders between 2010 and 2020. The outcome was the number of weeks from the last contact with services to suicide. The exposure was comorbid mental disorders divided into 'no comorbid mental disorder’; ‘psychosis or bipolar disorders’ (F20−F31), ‘depressive or anxiety disorders' (F32−F49); and 'personality disorders' (F60-F69). Covariates included gender, age, last diagnosed substance use disorder, registered deliberate self-harm last year, and the number of in- and outpatient contacts the previous year. Results The number of weeks from last service contact to suicide differed (p =  < 0.001) between patients with no comorbid mental disorders (Median = 7; IQR 2–23), psychosis or bipolar disorders (Median = 2; IQR = 1–7), depressive or anxiety disorders (Median = 3; IQR = 1–11) and personality disorders (Median = 1; IQR = 1–5.5). Significantly decreased adjusted incidence rate ratios (aIRR) were found for psychosis or bipolar disorders [aIRR = 0.67 (95% CI 0.53–0.85)] and personality disorders [aIRR = 0.56 (0.42–0.77)] compared to no comorbid mental disorder when adjusted for individual characteristics and service contact. For depressive and anxiety disorders compared to no comorbid mental disorder, the association was significant when adjusted for individual characteristics [aIRR = 0.55 (0.46–0.66)]. Conclusions While patients with substance use disorders generally died by suicide a short time after contact with services, patients with comorbid mental disorders died an even shorter time after such contact and significantly shorter than patients without such comorbidities.